A New Approach For Economic Evaluation Of In-Situ Mining Ventures (Society for Mining, Metallurgy & Exploration, 1985)
This paper presents a method for evaluating the economic feasibility of solution mining a hypothetical uranium roll-front deposit. It is assumed the wellfield will be operated in a prudent manner and that leaching tests were performed in depth in both lab and field (push-pull) prior to startup. Leach test results are reduced to two important parameters and used as the basis for solution mining a wellfield. This case study assumes a 10 mil- lion-lb uranium deposit with 40 possible small wellfields; four are kept in operation simultaneously until the deposit is depleted. The wellfields have different ore reserves and grades, lixiviant circulation rates, leach rates, and peak concentrations, and thus the daily uranium production will vary. Daily production is used to assess the profitability of a particular lixiviant and the mode of well- field operation in light of realistic market price estimates. The mathematical procedure is simple and straightforward, based on reasonable in-situ leaching relationships as well as accepted accounting practices.